The Effect of Self-Control on Sensation Seeking in Adolescents who Play Online Games in Makassar - Erdiansyah, Mochamad; Khumas, Asniar; Ismail, Ismalandari (Polteknik Ilmu Pemasyarakatan, 2023)
Sensation seeking is a personality trait that is expressed in a general tendency to seek sensations, varied experiences, new, complex, and willingness to take risks. This research aims to determine the effect of self-control on sensation seeking in teenagers who play online games in Makassar. Respondents in this study were 170 adolescents aged 13 - 18 who played online games in Makassar. Sampling using accidental sampling technique. Measuring tools used are self control scale and sensation seeking scale. This research uses quantitative methods. Data results using simple linear regression analisysis showed that was a negative effect of self-control on sensation seeking (β = -0.374, p = 0.40; p <0.05). The contribution of the influence of self-control to sensation seeking among teenagers who play online games in Makassar is 1.9% (Adjusted R2 = 0.19 and p = 0.000; p<0.05). This research shows that there is a significant influence of self-control on sensation seeking among teenagers addicted to online games in Makassar amounting to 0.19 (1.9%). Based on the results of the regression analysis test, it has a negative coefficient value of -0.374. This shows that the lower self-control, the higher the sensation seeking among teenagers addicted to online games in Makassar.